Remote Attestation on Program Execution - GU, Liang (Institutional Knowledge at Singapore Management University, 2008)
Remote attestation provides the basis for one platform to establish trusts on another. In this paper, we consider the problem of attesting the correctness of program executions. We propose to measure the target program and all the objects it depends on, with an assumption that the Secure Kernel and the Trusted Platform Module provide a secure execution environment through process separation. The attestation of the target program begins with a program analysis on the source code or the binary code in order to find out the relevant executables and data objects. Whenever such a data object is accessed or a relevant executable is invoked due to the execution of the target program, its state is measured for attestation. Our scheme not only testifies to a program's execution, but also supports fine-granularity attestations and information flow checking.